Situation Leadership of the School Administration Affecting the Core Competency of Teacher Under the Secondary Education Service Area Office Supanburi - Kanpakdee, Pornsawan (Journal of Dhamma for Life, 2025)
The purpose of this research were 1) to study situation leadership of the School administrator under the secondary service educational area office Suphanburi 2) to study the core competency of teacher under the secondary service educational area office Suphanburi and 3) to study situation leadership of the school administrator effecting the core competency of teacher under the secondary educational service area office Suphanburi Simple group in this research is the school director and the teacher under the secondary educational service area office Suphanburi, total of 317 informants. The instrument used in this study was questionnaires. The data was analyzed using package program. The statistics used in data analyzing were frequency, percentage, arithmetic mean, standard deviation, hypothesis test used the analysis stepwise multiple regression analysis. The results of this research were follows: 1) Situation leadership of the school administrator under the secondary educational service area office Suphanburi in overall was at the high level, ranking by arithmetic mean from the highest to the lowest; selling, telling, delegating and participating, respectively. 2) The core competency of teacher under the secondary educational service area office Suphanburi in overall was at the highest level, and each aspect were at the highest level too, ranking by arithmetic mean from the highest to the lowest; service mind, teacher’s ethics and integrity, self-development, team work, working achievement motivation, respectively. 3) Situation leadership of the school administrator effecting the core competency of teacher under the secondary educational service area office Suphanburi in overall was statistical significance at .01 level priorities are: delegating, participating, selling and telling. There was a multiple correlation coefficient (Multiple R) of .661, in which the variables discussed the variance of the core competency of teacher under the secondary educational service area office Suphanburi 66.1 percent (R 2 = .661), which can be written as a regression analysis equation as follows. Forecast equations in raw score form y ̂tot = 1.165 + .156 (X1) + .208 (X2) + .139 (X3) + .252 (X4) (R2 = .666) Forecast equations in standard score form z ̂y = .183 (Z_(x_1 )) + .230 (Z_(x_2 ) ) + .174 (Z_(x_3 ) ) + .315 (Z_(x_4 ) ) (R2 = . 666)